THE ROLE OF COPING STRATEGIES IN PREDICTING PSYCHOLOGICAL WELL-BEING AMONG NURSING STUDENTS - Endang Caturini Sulistyowati; Siti Khadijah; Dwi Ariani Sulistyowati (Bajang Institute, 2026)
Nursing students face complex academic and clinical demands, including academic pressure, exposure to critically ill patients, and professional competency requirements, which may negatively affect their psychological well-being. Adaptive coping strategies are considered important resources for maintaining psychological well-being; however, studies examining coping as a predictor of psychological well-being among nursing students remain limited. Objective: To investigate the predictive role of coping strategies on psychological well-being among nursing students while controlling for age, gender, and academic year. Methods: A quantitative study with a cross-sectional predictive correlational design was conducted among 241 nursing students selected through proportional random sampling from a population of 608 undergraduate nursing students. Data were collected using coping strategy and psychological well-being questionnaires. Hierarchical linear regression was employed to examine the predictive role of coping, controlling for age, gender, and academic year. Results: The control model, including age, gender, and academic year, was not a significant predictor of psychological well-being (R² = 0.020; p = 0.182). After coping was added, the explained variance increased significantly to R² = 0.139 (ΔR² = 0.118; ΔF = 32.398; p < 0.001). Coping emerged as a significant positive predictor of psychological well-being (β = 0.346; p < 0.001). Gender also contributed significantly (β = 0.170; p = 0.007), whereas age and academic year were not significant predictors. Conclusion: Adaptive coping significantly predicts psychological well-being among nursing students. Strengthening coping skills can be an effective strategy for promoting and maintaining students’ psychological well-being.